2021
DOI: 10.1016/j.clinthera.2021.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Sex- or Gender-specific Differences in the Clinical Presentation, Outcome, and Treatment of SARS-CoV-2

Abstract: This review describes the sex and gender differences in COVID-19 presentation, treatment, and outcomes. We discuss the differences between the sexes in susceptibility to infection, the role of sex chromosomes on the body's immunologic response and the influence of hormones on the body's response to the virus. Additionally, the sex differences in clinical and laboratory presentation, complications of infection and outcomes, as well as differences in response to treatment and prevention are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Known biological differences in adaptive and innate immune responses between sexes explain some of these observed differences (4). Socio-cultural gender constructs also influence these outcomes through differing exposures to the disease (such as high occupational exposure in frontline healthcare workers, who are predominantly women), risk factors for severe disease (such as higher smoking rates in men), existence of comorbidities, and engagement with healthcare services for prevention, detection, and treatment (typically lower in men) (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Known biological differences in adaptive and innate immune responses between sexes explain some of these observed differences (4). Socio-cultural gender constructs also influence these outcomes through differing exposures to the disease (such as high occupational exposure in frontline healthcare workers, who are predominantly women), risk factors for severe disease (such as higher smoking rates in men), existence of comorbidities, and engagement with healthcare services for prevention, detection, and treatment (typically lower in men) (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers and qualities (such as sex) in COVID-19 have been shown to manifest in negative disease outcomes (hospitalization, ICU, and mortality) and in differences in immune responses [ 11 ]. For example, age as an influence on comorbidities as a covariate for fatality is strongly sex specific [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, S protein has been chosen as an antigen for several approved vaccines worldwide [ 10 ]. Additionally, males have consistently shown to have higher mortality and hospitalization rates in comparison to females [ 11 ]. We are using male and female as synonymous for biological sex unless otherwise specified as gender.…”
Section: Introductionmentioning
confidence: 99%
“…The potential role for hormones in COVID-19 was also shown in an analysis of females using the COVID Symptom Tracker Application in the United Kingdom: this showed COVID-19 infections and hospitalisation were significantly lower in women aged 18–45 taking oral contraceptives compared with matched women not taking oral contraceptives [ 66 ]. Of course, there are gender-associated behaviours that may affect COVID-19 infections and mortalities, for instance males are more likely to be smokers which increases ACE2 expression [ 1 ]. Overall, there does appear to be a gender and hormone bias in the severity of COVID-19 infections.…”
Section: Gender and Covid-19mentioning
confidence: 99%
“…Rodent studies have shown that, throughout embryonic development and sexual maturation, the lung structure and functional output can be affected by ligands of the androgen receptor (AR) and glucocorticoid receptor (GR), and to a lesser extent oestrogen receptor (ER). There is increasing evidence of gender differences in terms of COVID severity and a potential role of hormones and their target nuclear receptors in mediating COVID infections [ 1 ]. Most notably, lung cell infection by the SARS-CoV-2 virus (which causes COVID-19), as well as related viruses, has been shown to be facilitated by host cell proteins regulated by steroid hormones, especially androgens.…”
Section: Introductionmentioning
confidence: 99%